2020
DOI: 10.21577/0100-4042.20170514
|View full text |Cite
|
Sign up to set email alerts
|

QUANTIFICATION OF BERGENIN, ANTIOXIDANT ACTIVITY AND NITRIC OXIDE INHIBITION FROM BARK, LEAF AND TWIG OF Endopleura uchi

Abstract: Phytochemical investigation of Endopleura uchi led to the isolation of a gallic acid derivate, known as bergenin (2) and friedelin (1), a pentacyclic triterpene. The present work also reports the bergenin quantification in different Endopleura uchi bark, twig and leaves extracts. Our findings showed the highest bergenin concentration in bark methanol extracts (4.75%) and the lowest concentration in twig aqueous extracts (1.89%). Phenolics quantification by Folin-Ciocalteu, revealed phenolic compounds level val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…From 180.1 to 236 mg of bergenin were found in 100 g of yellow uxi pulp (dry weight). In comparison with other parts of the E. uchi plant, the highest content of bergenin was found in the bark (4,170 -4,750 mg 100 g -1 ), twigs (2,660 -3,440 mg 100 g -1 ), and leaves (2,230 -3,870 mg 100 g -1 ) (Muniz et al 2020). Several in vivo and in vitro studies have shown biological activities of bergenin, such as neuroprotective (Takahashi et al 2003), hepatoprotective (Popov et al 2005), anti-inflammatory (Nunomura et al 2009), and anti-arthritic (Nazir et al 2007).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…From 180.1 to 236 mg of bergenin were found in 100 g of yellow uxi pulp (dry weight). In comparison with other parts of the E. uchi plant, the highest content of bergenin was found in the bark (4,170 -4,750 mg 100 g -1 ), twigs (2,660 -3,440 mg 100 g -1 ), and leaves (2,230 -3,870 mg 100 g -1 ) (Muniz et al 2020). Several in vivo and in vitro studies have shown biological activities of bergenin, such as neuroprotective (Takahashi et al 2003), hepatoprotective (Popov et al 2005), anti-inflammatory (Nunomura et al 2009), and anti-arthritic (Nazir et al 2007).…”
Section: Discussionmentioning
confidence: 87%
“…In the region of Belém, in the eastern Brazilian Amazon, yellow uxi is used for its timber, and its oil, fruits, and trunk bark are used in traditional medicines to treat arthritis, cholesterol, and sinusitis (Herrero-Jáuregui et al 2009;Shanley et al 2012). The bark of yellow uxi is rich in bergenin, a 4-O-methyl gallic acid C-glycoside derivate, which shows anti-inflammatory, antifungal, hepatoprotective, and neuroprotective activities (Bastos et al 2020;Muniz et al 2020;Machado et al 2010;Nunomura et al 2009;Pontes et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Besides antimicrobial activity, bergenin has also been pointed out as one of the main substances responsible for antimalarial [ 24 ], anti-inflammatory [ 48 , 49 ], antinociceptive [ 50 ], anxiolytic [ 51 ], and antioxidant activities [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drypetes tessmanniana, Putranjiva roxburghii, Uapaca ambanjensis, and Euphorbia tirucalli L. belonging to the family Euphorbiaceae; Salix tetrasperma and Populus davidiana belonging to the family Salicaceae; Terminalia avicennioides and Combretum duarteanum of the family Combretaceae; Luehea ochrophylla and Ancistrocarpus densispinosus of the family Tiliaceae; Prunus turfosa and Prunus lusitanica of the family Rosaceae and Maytenus ilicifolia and Maytenus aquifolium of family Celastraceae have been reported for the extraction of friedelin (Table 1). Salix tetrasperma Salicaceae 80% aqueous methanol [35] Calophyllum pinetorum Clusiaceae Sequentially with n-hexane and ethyl acetate [36] Drypetes tessmanniana Euphorbiaceae Methanol [37] Prunus turfosa Rosaceae 5% benzene in chloroform [38] Terminalia avicennioides Combretaceae Petroleum ether, ethyl acetate, chloroform, and methanol [40] Putranjiva roxburghii Euphorbiaceae Chloroform [41] Endopleura uchi Humiriaceae Hexane [42] Luehea ochrophylla Tiliaceae Hexane and ethanol [43] Ancistrocarpus densispinosus Oliv. Tiliaceae Methanol [44] Syzygium cumini L. Myrtaceae 70% methanol [45] Garcinia prainiana Clusiaceae n-hexane [27] Uapaca ambanjensis Euphorbiaceae Sequentially with n-hexane, dichloromethane, ethyl acetate, and methanol, respectively [46] Elaeocarpus floribundus Elaeocarpaceae Sequentially with hexane, chloroform, ethyl acetate, and methanol [47] Elytranthe parasitica Loranthaceae Methanol [48] Dombeya torrida Sterculiaceae Chloroform [49] Leaves Azima tetracantha Lam.…”
Section: Sources Of Friedelinmentioning
confidence: 99%